The Relevance of Economic Education To Contemporary Labor Market Demands - Atik Yuliana Sari; Anisa Riva Anggraeni; Rochanda Wiradinata; Rian Gunawan (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study aims to analyse the influence of the relevance of economic education on the needs of the world of work, specifically among alumni of the Economic Education Study Programme at Gunung Jati Swadaya University. The background to this study is based on the challenges of the era of digitalisation and industrial transformation, which require university graduates to have competencies that match the needs of the job market. This study uses a quantitative approach with a descriptive method. The sample in this study consists of 40 alumni selected through purposive sampling. The research instrument, a questionnaire, was distributed online and tested for validity and reliability before analysis. Data analysis techniques used include simple linear regression tests, correlation tests, determination coefficients, and significance tests (t-tests). The results of the study indicate that the relevance of economic education has a positive and significant effect on the needs of the job market, with a correlation coefficient of 0.737 and an R Square of 0.543, meaning that 54.3% of the job market needs are explained by this variable. This occurs with the rejection of H0 and the acceptance of Ha because the significance value of 0.000 is less than 0.05. This study combines Human Capital Theory and Job Matching Theory, demonstrating that relevant education can enhance graduates' readiness to face modern industrial challenges, contributing theoretically to understanding the relationship between education, skills, and work readiness. The findings emphasize the importance of developing competency-based curricula aligned with industrial needs, strengthening soft and hard skills, and optimising practical and internship programs such as MBKM. The recommendations from this study highlight the importance of synergy between educational institutions and the workforce in order to produce competent, adaptive, and competitive graduates in the labour market.Keywords: Relevance of Economic Education, World of Work Needs. Job suitability